The evaluation of a method to determine pollution performance curves for HTV-SR insulators tested under AC in a natural marine pollution environment - Davey, Richardo Lee (Stellenbosch : Stellenbosch University, 2025)
Davey, R. L. 2025. The Evaluation of a Method to Determine Pollution Performance Curves for HTV-SR Insulators Tested Under AC in a Natural Marine Pollution Environment. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/b5d0809d-338a-4cf5-b42f-13ed0da86b0c